How prevalent is post-decision dissonance? Some doubts and new evidence - Steinar Holden (University of Oslo, Department of Economics, 2009)
Recent research is exploring the case for cognitive or post-decision dissonance using the free-choice paradigm of Brehm (1956). Participants are repeatedly faced with a choice between items that they have given the same rating of liking, two items at a time, and it is found that items not chosen in one choice has a lower tendency of being chosen in a subsequent choice against a different alternative item. This tendency is interpreted as evidence for cognitive or post-decision dissonance. I argue that this interpretation of the evidence is invalid. Furthermore, I report a novel experiment in which participants were specifically asked to compare the items, allowing for a consistent interpretation of the evidence. I find no evidence of post-decision dissonance after a choice between items where one was viewed as more attractive than the other, but potentially some weak evidence of post-decision dissonance after a choice between items viewed as equally attractive.
Keywords: D03; 330; post-decision dissonance; cognitive dissonance; preferences; Verhaltensökonomik; Entscheidung; Psychologie; Kognition; Test